Sustainable Development: Implementation and Impact of Augmented Reality in Islamic History Learning - Almardiyah, Aina; Khalid, Essalihy; Fajri, Bayu Ramadhani; Akyuni, Quratul (Khalifa: Journal of Islamic Education, 2025)
This study aims to develop an Augmented Reality-based learning tool for Islamic history education in high schools. This research and development (R&D) adopts a six-stage approach: analysis, design, development, implementation, and evaluation (ADDIE). The resulting product has undergone rigorous validation by three experts in Augmented Reality, animation, and Islamic history education. Furthermore, this Augmented Reality-based learning material was tested on 120 students in four high schools. Student responses were carefully collected through questionnaires and analyzed using SPSS software version 26.0. The results showed that all experts agreed that the Augmented Reality product was valid and suitable for use as a learning medium. There are seven advantages to using this medium in learning, namely: the material is easy to understand, the content is clearly presented, the visual design is attractive, it provides a realistic learning experience, the learning experience is enjoyable, the Augmented Reality medium is easy to use, and there is a strong desire to return to learning using Augmented Reality. The use of this Augmented Reality-based learning module has significantly changed the learning experience of students to more concrete, enjoyable results and provided them with new experiences in Islamic history. These findings emphasize the need to continue designing and developing various Augmented Reality-based resources to strengthen the teaching of Islamic cultural history.